Pengaruh Pertumbuhan Perusahaan, Kepemilikan Manajerial dan Kebijakan Dividen Pada Kinerja Perusahaan Manufaktur di BEI - Kamajaya, I Wayan Diva Pradita; Dwija Putri, I G.A.M. Asri (E-Jurnal Akuntansi, 2019)
This research was conducted to analyze the influence of company growth, managerial ownership and dividend policy on company performance. The population in this study are companies listed on the Indonesian stock exchange Samples were taken using purposive sampling technique and obtained 8 samples that met the criteria with the number of observations as many as 40. Company performance was measured using the Tobin’s Q ratio. Hypothesis testing was carried out using multiple linear regression analysis. The resultsshowed that the company's growth and dividend policy were concluded that it had no effect on the company's performance. While managerial ownership policies have a positive effect on company performance. Keywords : company growth, managerial ownership, dividend policy